Expanding the notion of global learning: Turkish-Dutch teens’ networked configurations for learning - Ünlüsoy, Asli; de Haan, Mariëtte (Frontline Learning Research, 2020)
Digital technology facilitate interactions between learners and resources at a global level. New learner prototypes are therefore proposed, such as the notion of the global learner. In this paper, we argue that these prototypes of global learning often do not account for the variety of ways in which youth use technology and see themselves as learners. We take the example of Turkish-Dutch youth to show empirically how they represent an alternative for what is often seen as the prototype of what a global learner is. We combine ego-network methodology with in-depth interviews to provide a detailed account of how 25 Turkish-Dutch teens see themselves as learners, how they make use of technology to pursue their interests, how they reach out to others and media resources, and how they form selves in relation to the values and norms of their (transnational) community. Using the notion of ‘learner identity’, the study shows how these teens develop learner identities that are built on specific and culturally informed notions of ‘what a learning subject is’ that challenge the universality of the autonomous subjectivity implied in prototypical notions of the global learner. In addition, the study shows how through digital affordances, unique networked (trans)national connectivities are formed, which are informed by these teens’ specific socio-cultural position. We argue that by acknowledging these alternative ways of what a learning subject is, and how connections are formed, we can proactively incorporate them as useful models of global learning.